Audio files comparison with wavelet transform - Jiang, Chengjun (2023)
This is a project development-based project, a signal processing project, the purpose is to design a program that uses continuous wavelet transform (CWT) to achieve the recognition of audio similarity, mainly used to identify the similarity between audio with different file names or different audio formats Spend. Today, a piece of music in the world may have many instruments, some played by piano, some saxophone, some even synthesized by software... Or, a song has other covers in different languages, sometimes English, sometimes It's Chinese, sometimes Japanese. Nowadays, people often download many songs to listen to, but sometimes they download the same song repeatedly in different folders, sometimes give them different names, sometimes download the same song but in different formats. So the goal of this project is to find the same or similar songs, i.e. songs with the same name but different formats, or songs with different names and formats but actually the same format, and songs with the same music but played or sung by different instruments/languages. This project will compare their similarities in MATLAB.